Integrative Efforts in Handling Plastic Pollution in Jakarta Bay: Social Capital and Movements - Khurin Nabillah (Journal of Maritime Studies and National Integration, 2022)
Jakarta Bay is the storefront for maritime activities in Indonesia. Littering in Jakarta Bay is a significant problem in the development of Jakarta. Although Jakarta has a large social capital, the actualisation of social capital in solving the waste problem in Jakarta Bay is still not widely known. This study analyses the strategy for implementing social capital for the people of Jakarta in handling plastic waste in Jakarta Bay from the perspective of maritime environmental security. The study used a descriptive qualitative method. Data were collected through observation, interviews and literature studies. Interviews were conducted with the government representatives, seamen and other relevant stakeholders. The results show that the impact of plastic waste in Jakarta Bay has disrupted shipping safety; the implementation of social capital for handling plastic waste in Jakarta Bay is carried out through the Waste Bank, Citizen Relations Management, Joint Responsibility Garbage and Jakarta Recycle Center (Sampah Tanggung Jawab Bersama /Samtama) and Jakarta Recycle programs Center. In handling waste at sea, the Jakarta Government cannot work alone; it needs to collaborate with the surrounding governments, including the governments of Bekasi, Tangerang and Banten Province. The achievement of increasing the participation of social capital and business actors actively reducing environmentally friendly waste and transforming waste into an economical source. Several ways are undertaken, including reducing source waste, optimising the Bantargebang TPST and building an Intermediate Treatment Facility.